(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The objective of this paper is to analyze theimpact of different components of compensation on the motivation level ofemployees in the banking sector. For the purpose of study, the compensation hasbeen classified into five components namely Basic salary, Short-termincentives, Long-term incentives, Benefits & services and Perquisites.Convenient sampling technique has been used to collect data from both publicand private sector banks. The principal statistical tools used for dataanalysis are mean, standard deviation and t-test. The results of the studyreveal that a significant difference exists in the motivation level of theemployees of public and private sector banks at different managerial levelswith regard to various compensation components.